Measurement of psychophysical quantities of air‐flow stimulus. (June 2017) - Takahashi, Haruka; Bando, Shizuka; Oiwa, Kosuke; Nozawa, Akio; Ishikawa, Tomoharu; Mitsui, Minoru
Abstract : Broadband audio devices appear to give a deeper sense of realism as an air field by making one feel the vibration of the air through the entire body. The application of the new media of information transfer and content of sense presentation is expected to reproduce this air field. The purpose of this study was to create a completely new sense with the air‐flow stimulus, termed 'air‐sensation'. In this study, we measured psychophysical quantities to clarify the sense properties of air‐sensation. Consequently, it was revealed that sense properties vary with the properties of signal waveform, stimulus‐presentation site, and stimulus‐presentation order. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.